2019
DOI: 10.1111/jop.12867
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of craniomaxillofacial fibro‐osseous lesions: A systematic review

Abstract: The purpose of this study was to perform a systematic review of the literature concerning all documented cases of malignant transformation of craniomaxillofacial fibro‐osseous lesions (FOLs). Three electronic databases were searched. Data were evaluated descriptively. Kaplan‐Meier survival curves were constructed and compared using the log‐rank test. A critical appraisal of included articles was performed through the Joanna Briggs Institute tool. A total of 19 studies including 27 patients were selected for da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Unfortunately, the paraffine blocks were not available anymore to perform such immunohistochemical stains in our two patients. There are various case reports and reviews of OSJ developing from fibrous dysplasia in low grade OSs ( 13 - 15 ). Probably some, if not many, of the reported cases have been an osteosarcoma right from the beginning as probably has been the case in our patient #2.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the paraffine blocks were not available anymore to perform such immunohistochemical stains in our two patients. There are various case reports and reviews of OSJ developing from fibrous dysplasia in low grade OSs ( 13 - 15 ). Probably some, if not many, of the reported cases have been an osteosarcoma right from the beginning as probably has been the case in our patient #2.…”
Section: Resultsmentioning
confidence: 99%
“…Malignant transformation accounts for 0.4e1.0% of all FD cases. 6,7 A case series of 266 patients with a definitive diagnosis of FD in a Chinese population showed that malignant transformations only occurred in three patients with polyostotic forms. 7 Another case series from Mayo Clinic of 1122 cases with a histological diagnosis of FD had malignant transformations in 19 cases of monostotic FD and 9 cases of polyostotic FD.…”
Section: Sirmentioning
confidence: 99%
“…8 The most common malignant changes are osteosarcoma, chondrosarcoma and fibrosarcoma. 6 Two case series have suggested a relationship with prior radiation, but most of the other case series have not investigated this relationship. 8,9 FD is associated with activating missense mutations in GNAS (20q13).…”
Section: Sirmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Although uncommon, malignant transformation of fibrous dysplasia has been well described, and any sudden change in size of the lesion should alert the clinician to this possibility. 7 Ossifying fibroma is an uncommon lesion that presents with similar radiological characteristics to those of fibrous dysplasia, except that the margins are well defined. A more aggressive variant can be found in the paediatric population (juvenile aggressive ossifying fibroma), and the primary treatment for all forms of ossifying fibroma is surgical excision.…”
Section: Fibro-osseous Lesions Of the Jawsmentioning
confidence: 99%